2012
DOI: 10.1371/journal.pone.0039184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Variation at the SLC6A3 Locus Predicts Lifetime Risk of PTSD in the Detroit Neighborhood Health Study

Abstract: Recent work suggests that the 9-repeat (9R) allele located in the 3′UTR VNTR of the SLC6A3 gene increases risk of posttraumatic stress disorder (PTSD). However, no study reporting this association to date has been based on population-based samples. Furthermore, no study of which we are aware has assessed the joint action of genetic and DNA methylation variation at SLC6A3 on risk of PTSD. In this study, we assessed whether molecular variation at SLC6A3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 36 publications
4
49
1
2
Order By: Relevance
“…The role of dopamine in the pathogenesis of PTSD has been supported by outcomes of elevated urinary and plasma levels in dopamine-related disorders (Chang et al, 2012). Additionally, there is a significant link between dopamine concentration and symptom severity (Chang et al, 2012). Our findings showed that maternal PTSD reduced the dopamine levels in the offspring, in accordance with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The role of dopamine in the pathogenesis of PTSD has been supported by outcomes of elevated urinary and plasma levels in dopamine-related disorders (Chang et al, 2012). Additionally, there is a significant link between dopamine concentration and symptom severity (Chang et al, 2012). Our findings showed that maternal PTSD reduced the dopamine levels in the offspring, in accordance with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…A previous report showed that 5-HT levels were lower in the rat hippocampus and prefrontal cortex (PFC) in a predator exposure/psychosocial stress model of PTSD (Wilson et al, 2014). The role of dopamine in the pathogenesis of PTSD has been supported by outcomes of elevated urinary and plasma levels in dopamine-related disorders (Chang et al, 2012). Additionally, there is a significant link between dopamine concentration and symptom severity (Chang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis covered eight CpGs, with the NGFI-A consensus binding sequence encompassing CpG positions 3 and 4. Because glucocorticoid-related changes in memory formation were repeatedly found to be more pronounced in men (Andreano and Cahill, 2006;Preuss and Wolf, 2009), we also considered possible gender differences in the present study. We first compared DNA methylation between genders and found significant differences between men and women at several CpG positions ( p Ͻ 0.05, e.g., methylation levels at NR3C1_CpG3 were significantly higher in women than in men, p ϭ 0.01).…”
Section: Dna Methylation Of the Nr3c1 Promoter In Traumatized Survivomentioning
confidence: 99%
“…Human studies have shown that the memory-enhancing effects of stress-induced elevations of glucocorticoids are usually more pronounced in men (Andreano and Cahill, 2006;Preuss and Wolf, 2009;Cornelisse et al, 2011). Furthermore, there is evidence that glucocorticoids impair the retrieval of memory processes (de Quervain et al, 2009).…”
Section: Introductionmentioning
confidence: 99%